Inhibition by cyclosporin A of Adenosine triphosphate-dependent transport from the hepatocyte into bile - Kadmon, Martina; Klünemann, Cornelia; Böhme, Matthias; Ishikawa, Toshihisa; Gorgas, Karin; Otto, Gerd; Herfarth, Christian; Keppler, Dietrich (Gastroenterology, 1993)
Background: Immunosuppressive treatment with cyclosporin A may be associated with impaired hepatobiliary elimination of bile salts and with cholestasis. Inhibition by cyclosporin A of the primary-active adenosine triphosphate (ATP)-dependent transport systems responsible for excretion of bile salts and cysteinyl leukotrienes across the hepatocyte canalicular membrane into bile may explain the cholestatic side effect. Methods: ATP-dependent transport of bile salt and of cysteinyl leukotrienes was studied in human liver plasma membrane vesicles and additionally in rat liver plasma membrane vesicles enriched in canalicular membranes. Results: Inhibition of ATP-dependent taurocholate transport in human liver by 50% was measured at 3 μmol/L cyclosporin A and at 4 μmol/L fujimycin. Kinetic analyses in rat liver indicated non-competitive inhibition by cyclosporin A with respect to ATP and competitive inhibition with respect to taurocholate with inhibition constant (Ki) values of 1.0 and 0.3 μmol/L, respectively. Conclusions: The ATP-dependent export carriers for bile salts and cysteinyl leukotrienes in the hepatocyte canalicular membrane are novel targets for inhibitory side effects of cyclosporin A. Inhibition of ATP-dependent bile salt transport may induce cholestasis.